Optimized distributed generation planning for radial distribution system using particle swarm optimization algorithm - Faruque, Fairuj Binte; Nazim, Md. Shahriar; Chowdhury, Shuva; Sowmitra, Mycheal (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.